Detecting fossil fuel emissions patterns from subcontinental regions using North American in situ CO2 measurements. Issue 12 (24th June 2014) - Shiga, Yoichi P.; Michalak, Anna M.; Gourdji, Sharon M.; Mueller, Kim L.; Yadav, Vineet
Abstract The ability to monitor fossil fuel carbon dioxide (FFCO2) emissions from subcontinental regions using atmospheric CO2 observations remains an important but unrealized goal. Here we explore a necessary but not sufficient component of this goal, namely, the basic question of the detectability of FFCO2 emissions from subcontinental regions. Detectability is evaluated by examining the degree to which FFCO2 emissions patterns from specific regions are needed to explain the variability observed in high‐frequency atmospheric CO2 observations. Analyses using a CO2 monitoring network of 35 continuous measurement towers over North America show that FFCO2 emissions are difficult to detect during nonwinter months. We find that the compounding effects of the seasonality of atmospheric transport patterns and the biospheric CO2 flux signal dramatically hamper the detectability of FFCO2 emissions. Results from several synthetic data case studies highlight the need for advancements in data coverage and transport model accuracy if the goal of atmospheric measurement‐based FFCO2 emissions detection and estimation is to be achieved beyond urban scales.